Failure analysis method for positive electrode active material of lithium ion battery
By comparing the mass proportion of cobalt oxide after freshness and cycle testing of lithium-ion batteries, the problem of quantitative analysis of the cathode material failure of lithium-ion batteries was solved, and quantitative characterization of the structural degradation of lithium-cobalt oxide materials was achieved, and data to improve battery performance was provided. support.
Patent Information
- Application Number
- CN202411473509.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-21
- Publication Date
- 2025-01-10
AI Technical Summary
The prior art cannot quantitatively analyze and characterize the failure of the positive electrode active material of lithium ion batteries, especially under high voltage conditions, the structural degradation of lithium cobalt oxide positive electrode material is serious, resulting in a decline in battery performance.
By comparing the mass proportion of cobalt oxide in the positive electrode active materials of lithium-ion batteries after fresh and cyclic testing, the structural degradation degree was calculated, and the lithium cobalt oxide and cobalt oxide were separated by physical and chemical methods for quantitative testing, and the mass proportion of cobalt oxide was obtained. Compared to characterize material failure.
Quantitative analysis and characterization of the failure of the positive electrode active material of lithium-ion batteries is realized, providing guidance on improving material performance, reducing testing costs and complexity, and improving the targeted nature of battery performance selection and improvement direction.
Smart Images

Figure CN119290651A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of lithium-ion batteries, and in particular to a method for analyzing failure of positive electrode active materials of lithium-ion batteries. Background Art
[0002] With the continuous development of the consumer electronics field, people have put forward higher requirements for the performance indicators of lithium-ion batteries. At present, high-voltage lithium cobalt oxide cathode materials (LCO) have been developed in the application field of cut-off voltage 4.53V (volts) +. With the increase of cut-off voltage, the failure problem of lithium cobalt oxide cathode materials has become more serious.
[0003] At a high operating voltage with a cut-off voltage higher than 4.55V, the O3-H1-3 phase transition of the lithium cobalt oxide cathode material is accompanied by more irreversible slip of the Co-O layer. Compared with the bulk phase, the surface structure is more severely damaged, such as O (oxygen) escape, Co (cobalt) dissolution and interface solvent decomposition. At the same time, the surface will undergo structural degradation that is completely opposite to the LCO synthesis process, that is, LiCoO2→Co3O4→ CoO. Therefore, it is very necessary to conduct failure analysis at the cathode active material level for failed cells and improve the performance of high-voltage lithium cobalt oxide batteries through material modification.
[0004] Related technologies using non-destructive analysis such as DQ / DV (capacity-voltage curve) and DV / DQ (voltage-capacity curve) can only conduct preliminary analysis of the macroscopic failure of positive electrode active materials. The test characterization of positive electrode active materials using XPS (X-ray photoelectron spectroscopy) / TEM (transmission electron microscopy) is too microscopic and has little guiding significance for the improvement of positive electrode active materials. In addition, the testing cost is high, making it difficult to use it as a routine means of failure analysis of positive electrode active materials.
[0005] Therefore, the related technologies for failure analysis of positive electrode active materials of lithium-ion batteries cannot quantitatively analyze the failure of positive electrode active materials of lithium-ion batteries, and cannot quantitatively characterize the failure of positive electrode active materials of lithium-ion batteries. Summary of the invention
[0006] In order to solve or partially solve the problems existing in the related art, the present application provides a method for analyzing failure of positive electrode active materials of lithium ion batteries, which can quantitatively analyze the failure of positive electrode active materials of lithium ion batteries and quantitatively characterize the failure of positive electrode active materials of lithium ion batteries.
[0007] The first aspect of the present application provides a method for analyzing failure of a positive electrode active material of a lithium ion battery, the method comprising: Obtain a first group of lithium-ion batteries and a second group of lithium-ion batteries, wherein the first group of lithium-ion batteries includes a group of fresh fully-charged lithium-ion batteries that have not been cycled tested, and the second group of lithium-ion batteries includes another group of fresh fully-charged lithium-ion batteries that have been cycled tested; The degree of structural degradation of the positive electrode active material characterizing failure of the positive electrode active material of the lithium ion battery is calculated based on a first mass ratio of cobalt oxide in the positive electrode active material of the first group of lithium ion batteries and a second mass ratio of cobalt oxide in the positive electrode active material of the second group of lithium ion batteries.
[0008] Preferably, before calculating the degree of structural degradation of the positive electrode active material characterizing failure of the positive electrode active material of the lithium ion battery according to the first mass proportion of cobalt oxide in the positive electrode active material of the first group of lithium ion batteries and the second mass proportion of cobalt oxide in the positive electrode active material of the second group of lithium ion batteries, the method comprises: Obtaining a first material to be tested from the positive electrode active materials of the first group of lithium-ion batteries; According to the first material to be tested, obtaining the first mass ratio; Obtaining a second material to be tested from the positive electrode active material of the second group of lithium-ion batteries; According to the second material to be tested, the second mass ratio is obtained.
[0009] Preferably, the step of obtaining the first material to be tested in the positive electrode active material of the first group of lithium-ion batteries includes: Scraping powder from the positive electrode sheets of the first group of lithium-ion batteries to separate the coating of the positive electrode sheets from the positive electrode current collector to obtain a first powder material of the first group of lithium-ion batteries; Dispersing the first powder in an organic solvent to obtain a first mixed solution of the first group of lithium-ion batteries; The first mixed solution is allowed to stand for a set standing time, so that the first mixed solution is separated into an upper layer solution and a lower layer solution; removing the upper layer solution of the first mixed solution, retaining the lower layer solution of the first mixed solution, and performing solid-liquid separation on the lower layer solution of the first mixed solution by centrifugation to obtain first powder particles of the first group of lithium-ion batteries; Dispersing the first powder particles in ethanol to obtain a first ethanol mixed solution of the first group of lithium-ion batteries; Centrifugally separating the first ethanol mixed solution to obtain first solid particles of the first ethanol mixed solution, and using the first solid particles as the first material to be tested; and / or, The step of obtaining the second material to be tested from the positive electrode active material of the second group of lithium-ion batteries comprises: Scraping powder from the positive electrode sheets of the second group of lithium-ion batteries to separate the coating on the positive electrode sheets of the second group of lithium-ion batteries from the positive electrode current collector to obtain a second powder material for the second group of lithium-ion batteries; Dispersing the second powder in an organic solvent to obtain a second mixed solution of the second group of lithium-ion batteries; The second mixed solution is allowed to stand for a set standing time, so that the second mixed solution is separated into an upper layer solution and a lower layer solution; removing the upper layer solution of the second mixed solution, retaining the lower layer solution of the second mixed solution, and performing solid-liquid separation on the lower layer solution of the second mixed solution by centrifugation to obtain second powder particles of the second group of lithium-ion batteries; Dispersing the second powder particles in ethanol to obtain a second ethanol mixed solution of the second group of lithium ion batteries; The second ethanol mixed solution is centrifuged to obtain second solid particles of the second ethanol mixed solution, and the second solid particles are used as the second material to be tested.
[0010] Preferably, obtaining the first mass ratio according to the first material to be tested includes: Mixing the first material to be tested with a first hydrochloric acid solution and performing a first heating treatment to prepare a first mixed solution of the first group of lithium-ion batteries; Using a filter membrane to filter the first mixed solution to obtain a residue of the first mixed solution; Using high-purity water to rinse the residue of the first mixed solution and the filter membrane for a set number of times; The residue of the first mixed solution after washing is mixed with the filter membrane and the second hydrochloric acid solution, and subjected to a second heating treatment to obtain a third mixed solution of the first group of lithium-ion batteries; Mixing the third mixed solution with a perchloric acid solution, and performing a third heating treatment to allow the third mixed solution and the perchloric acid solution to fully react, thereby obtaining a first test solution of the first group of lithium-ion batteries; Obtaining a first cobalt content of the cobalt element in the first test solution; calculating the first mass proportion according to the first cobalt content, the volume of the first test liquid, and the mass of the first test material; and / or, The step of obtaining the second mass ratio according to the second material to be tested includes: Mixing the second material to be tested with the first hydrochloric acid solution and performing a first heating treatment to prepare a second mixed solution of the second group of lithium-ion batteries; Using a filter membrane to filter the second mixed liquid to obtain a residue of the second mixed liquid; Using high-purity water to rinse the residue of the second mixed solution and the filter membrane for a set number of times; Mixing the residue of the second mixed solution after washing with the filter membrane and the second hydrochloric acid solution, and performing a second heating treatment to obtain a fourth mixed solution of the second group of lithium-ion batteries; Mixing the fourth mixed solution with a perchloric acid solution, and performing a third heating treatment to allow the fourth mixed solution and the perchloric acid solution to fully react, thereby obtaining a second test solution of the second group of lithium-ion batteries; Obtaining a second cobalt content of the cobalt element in the second test solution; The second mass proportion is calculated according to the second cobalt content, the volume of the second test liquid, and the mass of the second test material.
[0011] Preferably, calculating the first mass ratio according to the first cobalt content, the volume of the first test liquid, and the mass of the first test material includes: The first mass proportion ω1 is calculated using the following formula: ω1(%)=0.1365×(M1)×(V1)×(m1); Wherein, M1 represents the first cobalt content, V1 represents the volume of the first test liquid, and m1 represents the mass of the first test material; and / or, The calculating the second mass proportion according to the second cobalt content, the volume of the second test liquid, and the mass of the second test material includes: The second mass proportion ω2 is calculated using the following formula: ω2(%)=0.1365×(M2)×(V2)×(m2); In the formula, M2 represents the second cobalt content, V2 represents the volume of the second test liquid, and m2 represents the mass of the second test material.
[0012] Preferably, the organic solvent includes one or more of nitrogen-methyl pyrrolidone, acetone, dimethylformamide, dimethylacetamide, and anhydrous ethanol.
[0013] Preferably, the mass percentage concentration of the first hydrochloric acid solution is 20% to 25%; The first heating temperature of the first heating treatment is 100° C. to 150° C., and the first heating time of the first heating treatment is 30 min to 50 min. Preferably, the ratio of the mass of the first material to be tested to the volume of the first hydrochloric acid solution is 0.05 to 0.075; The ratio of the mass of the second material to be tested to the volume of the first hydrochloric acid solution is 0.05 to 0.075; wherein, The unit of the mass of the first material to be tested and the unit of the mass of the second material to be tested is gram, and the unit of the volume of the first hydrochloric acid solution is milliliter.
[0014] Preferably, the filter membrane is a water filter membrane, and the pore size of the filter membrane is 0.1 μm to 1.0 μm.
[0015] Preferably, the mass percentage concentration of the second hydrochloric acid solution is 25% to 30%; The second heating temperature of the second heating treatment is 200° C. to 400° C., and the second heating time of the second heating treatment is 30 min to 50 min.
[0016] Preferably, the mass percentage concentration of the perchloric acid solution is 65% to 70%; The third heating temperature of the third heat treatment is 500°C to 800°C.
[0017] Preferably, the ratio of the mass of the first material to be tested to the volume of the perchloric acid solution is 0.25 to 0.5; The ratio of the mass of the second material to be tested to the volume of the perchloric acid solution is 0.25 to 0.5; wherein, The unit of the mass of the first material to be tested and the unit of the mass of the second material to be tested is gram, and the unit of the volume of the perchloric acid solution is milliliter.
[0018] The technical solution provided by this application may have the following beneficial effects: The technical solution of the present application calculates the degree of structural degradation of the positive electrode active material of the lithium ion battery after the cycle test by the mass proportion of cobalt oxide in the positive electrode active material of the lithium ion battery before the cycle test and after the cycle test. The greater the degree of structural degradation of the positive electrode active material, the more serious the failure of the positive electrode active material; quantitatively analyzes the degree of structural degradation of the phase structure of the positive electrode active material (lithium cobalt oxide) of the lithium ion battery after the cycle test, can quantitatively analyze the failure of the positive electrode active material of the lithium ion battery, quantitatively characterize the failure of the positive electrode active material of the lithium ion battery, can have a strong guiding significance for the improvement direction of the positive electrode active material, provide data support for the improvement of the positive electrode active material of the lithium ion battery, and make the selection of the positive electrode active material in the lithium ion battery cell system and the improvement direction of the positive electrode active material more targeted.
[0019] It should be understood that the foregoing general description and the following detailed description are exemplary and explanatory only and are not restrictive of the present application. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] The above and other objects, features and advantages of the present application will become more apparent by describing in more detail exemplary embodiments of the present application in conjunction with the accompanying drawings, wherein the same reference numerals generally represent the same components in the exemplary embodiments of the present application.
[0021] Figure 1 It is a schematic flow chart of a method for analyzing failure of positive electrode active materials of a lithium-ion battery shown in an embodiment of the present application; Figure 2 1 is another schematic flow chart of a method for analyzing failure of a positive electrode active material of a lithium-ion battery shown in an embodiment of the present application; Figure 3 It is a schematic diagram of the structure of an electronic device shown in an embodiment of the present application. DETAILED DESCRIPTION
[0022] The embodiments of the present application will be described in more detail below with reference to the accompanying drawings. Although the embodiments of the present application are shown in the accompanying drawings, it should be understood that the present application can be implemented in various forms and should not be limited by the embodiments described herein. On the contrary, these embodiments are provided to make the present application more thorough and complete, and to fully convey the scope of the present application to those skilled in the art.
[0023] The terms used in this application are for the purpose of describing specific embodiments only and are not intended to limit this application. The singular forms of "a", "said" and "the" used in this application and the appended claims are also intended to include plural forms unless the context clearly indicates other meanings. It should also be understood that the term "and / or" used herein refers to and includes any or all possible combinations of one or more associated listed items.
[0024] It should be understood that although the terms "first", "second", "third", etc. may be used in this application to describe various information, this information should not be limited to these terms. These terms are only used to distinguish the same type of information from each other. For example, without departing from the scope of this application, the first information may also be referred to as the second information, and similarly, the second information may also be referred to as the first information. Thus, the features defined as "first" and "second" may explicitly or implicitly include one or more of the features. In the description of this application, the meaning of "multiple" is two or more, unless otherwise clearly and specifically defined.
[0025] The embodiment of the present application provides a method for analyzing failure of positive electrode active materials of lithium ion batteries, which can quantitatively analyze the failure of positive electrode active materials of lithium ion batteries and quantitatively characterize the failure of positive electrode active materials of lithium ion batteries.
[0026] The technical solution of the embodiments of the present application is described in detail below with reference to the accompanying drawings.
[0027] Figure 1 It is a schematic diagram of the process of the failure analysis method of the positive electrode active material of a lithium-ion battery shown in the embodiment of the present application.
[0028] See also Figure 1 , a method for analyzing failure of positive electrode active materials of lithium-ion batteries, comprising: Step 110, obtaining a first group of lithium-ion batteries and a second group of lithium-ion batteries, wherein the first group of lithium-ion batteries includes a group of fresh fully-charged lithium-ion batteries that have not been cycled tested, and the second group of lithium-ion batteries includes another group of fresh fully-charged lithium-ion batteries that have undergone cycle testing.
[0029] Step 120, calculating a degree of structural degradation of the positive electrode active material characterizing failure of the positive electrode active material of the lithium ion battery according to a first mass ratio of cobalt oxide in the positive electrode active material of the first group of lithium ion batteries and a second mass ratio of cobalt oxide in the positive electrode active material of the second group of lithium ion batteries.
[0030] In one embodiment, the fresh fully-charged lithium-ion batteries of the first group of lithium-ion batteries and the fresh fully-charged lithium-ion batteries of the second group of lithium-ion batteries can be fresh fully-charged lithium-ion batteries of the same system and model prepared using the same battery components such as the same positive electrode plate, separator, negative electrode plate, electrolyte, etc.; one group of fresh fully-charged lithium-ion batteries is selected as the first group of lithium-ion batteries, and another group of fresh fully-charged lithium-ion batteries is selected as the second group of lithium-ion batteries after cycle testing, wherein the fresh fully-charged lithium-ion batteries of the first group of lithium-ion batteries are new fully-charged lithium-ion batteries that have not been subjected to cycle testing.
[0031] In one embodiment, the coating of the positive electrode plates of the first group of lithium-ion batteries and the second group of lithium-ion batteries can be separated from the positive electrode collector, and the positive electrode active material in the coating of the positive electrode plates can be obtained; the first mass proportion of cobalt oxide in the positive electrode active material of the first group of lithium-ion batteries can be obtained; and the second mass proportion of cobalt oxide in the positive electrode active material of the second group of lithium-ion batteries can be obtained.
[0032] The method for analyzing failure of positive electrode active materials of lithium ion batteries in the embodiments of the present application calculates the degree of structural degradation of the positive electrode active materials of the lithium ion batteries after the cycle test by the mass proportion of cobalt oxide in the positive electrode active materials of the lithium ion batteries before and after the cycle test. The greater the degree of structural degradation of the positive electrode active materials, the more serious the failure of the positive electrode active materials. The degree of structural degradation of the positive electrode active materials (lithium cobalt oxide) of the lithium ion batteries after the cycle test is quantitatively analyzed, and the failure of the positive electrode active materials of the lithium ion batteries can be quantitatively analyzed and quantitatively characterized. It can have a strong guiding significance for the improvement direction of the positive electrode active materials of the lithium ion batteries, provide data support for the improvement of the positive electrode active materials of the lithium ion batteries, and make the selection of positive electrode active materials in the lithium ion battery cell system and the improvement direction of the positive electrode active materials more targeted.
[0033] Figure 2 It is another schematic flow chart of the failure analysis method of the positive electrode active material of a lithium-ion battery shown in the embodiment of the present application.
[0034] See also Figure 2 , a method for analyzing failure of positive electrode active materials of lithium-ion batteries, comprising: Step 210, obtaining a first group of lithium-ion batteries and a second group of lithium-ion batteries, wherein the first group of lithium-ion batteries includes a group of fresh fully-charged lithium-ion batteries, and the second group of lithium-ion batteries includes another group of fresh fully-charged lithium-ion batteries after cycle testing.
[0035] In one embodiment, the fresh fully-charged lithium-ion batteries of the first group of lithium-ion batteries and the fresh fully-charged lithium-ion batteries of the second group of lithium-ion batteries can be fresh fully-charged lithium-ion batteries of the same system and model prepared using the same battery components such as the same positive electrode plate, separator, negative electrode plate, electrolyte, etc.; one group of fresh fully-charged lithium-ion batteries is selected as the first group of lithium-ion batteries, and another group of fresh fully-charged lithium-ion batteries is selected as the second group of lithium-ion batteries after cycle testing, wherein the fresh fully-charged lithium-ion batteries of the first group of lithium-ion batteries are new fully-charged lithium-ion batteries that have not been subjected to cycle testing.
[0036] In one embodiment, the fresh fully-charged lithium-ion battery can be an unused fully-charged lithium-ion battery of the same system and model, which is prepared by using the same battery components such as the same positive electrode plate, separator, negative electrode plate, electrolyte, etc. through the steps of stacking, winding, shelling, liquid injection, formation, and capacity separation.
[0037] In one embodiment, a fresh, fully charged lithium-ion battery can be subjected to a cycle test at 45° C. to obtain a second group of lithium-ion batteries after the cycle test; wherein the cycle test includes but is not limited to: 1.2C constant current and constant voltage charging to 4.53V, 0.05C cut-off, 0.7C discharge to 3V, and 400 cycles.
[0038] Step 220 , respectively obtain a first material to be tested of the first group of lithium-ion batteries and a second material to be tested of the second group of lithium-ion batteries.
[0039] In one embodiment, a first material to be tested in the positive electrode active material of the first group of lithium-ion batteries can be obtained according to the positive electrode sheet of the first group of lithium-ion batteries; the steps include: Step 2211, scrape powder from the positive electrode plates of the first group of lithium-ion batteries, separate the coating of the positive electrode plates from the positive electrode collector, and obtain the first powder material of the first group of lithium-ion batteries.
[0040] In one embodiment, the soft-pack cells of the first group of lithium-ion batteries can be disassembled to obtain the positive electrode sheets of the first group of lithium-ion batteries; the positive electrode sheets of the first group of lithium-ion batteries are powdered, and the coating on the positive electrode sheets is separated from the foil (positive electrode current collector) using a ceramic knife to obtain the first powder of the first group of lithium-ion batteries.
[0041] In one embodiment, the area (e.g., 50 cm 2 (square centimeters) ~ 100cm 2 ) is scraped for powder, and a ceramic knife is used to separate the coating and foil on the positive electrode sheet of a set area to obtain the first powder material of the first group of lithium-ion batteries.
[0042] Step 2212, dispersing the first powder in an organic solvent to obtain a first mixed solution of a first group of lithium-ion batteries.
[0043] Step 2213, allowing the first mixed solution to stand for a set standing time, so that the first mixed solution is separated into an upper layer solution and a lower layer solution.
[0044] Step 2214, removing the upper layer solution of the first mixed solution, retaining the lower layer solution of the first mixed solution, and performing solid-liquid separation on the lower layer solution of the first mixed solution by centrifugation to obtain first powder particles of the first group of lithium-ion batteries.
[0045] In one embodiment, the first powder of the first group of lithium-ion batteries can be immersed in an organic solvent, and ultrasonic stirring is used to perform a first sufficient stirring to obtain a first mixed solution of the first group of lithium-ion batteries, wherein the ultrasonic frequency range of the ultrasonic stirring is 15KHz (kilohertz) to 50KHz, and the stirring time of the ultrasonic stirring is 3h (hour) to 6h; the first mixed solution is allowed to stand for 0.5h to 1h to separate the first mixed solution into layers; after standing, the first mixed solution is separated into an upper solution and a lower solution, wherein the upper solution is a conductive agent and the lower solution is a positive electrode active material; the upper solution of the first mixed solution is removed by a rubber-tipped dropper, and the lower solution of the first mixed solution is retained; the lower solution of the first mixed solution is centrifuged by a centrifuge to separate the solid and liquid of the lower solution of the first mixed solution, and the first powder particles of the lower solution of the first mixed solution are obtained.
[0046] Step 2215, dispersing the first powder particles in ethanol to obtain a first ethanol mixed solution of a first group of lithium-ion batteries.
[0047] Step 2216, centrifugally separate the first ethanol mixed solution to obtain first solid particles of the first ethanol mixed solution, and use the first solid particles as the first material to be tested.
[0048] In one embodiment, the first powder of the first group of lithium-ion batteries can be immersed in an organic solvent, and ultrasonic stirring is used to perform a first sufficient stirring to obtain a first mixed solution of the first group of lithium-ion batteries, wherein the ultrasonic frequency range of the ultrasonic stirring is 15KHz (kilohertz) to 50KHz, and the stirring time of the ultrasonic stirring is 3h (hour) to 6h; the first mixed solution is allowed to stand for 0.5h to 1h to separate the first mixed solution into layers; after standing, the first mixed solution is separated into an upper solution and a lower solution, wherein the upper solution is a conductive agent and the lower solution is a positive electrode active material; the upper solution of the first mixed solution is removed by a rubber-tipped dropper, and the lower solution of the first mixed solution is retained; the lower solution of the first mixed solution is centrifuged by a centrifuge to separate the solid and liquid of the lower solution of the first mixed solution, and the first powder particles of the lower solution of the first mixed solution are obtained.
[0049] In one embodiment, the first powder particles of the lower layer solution of the first mixed solution can be immersed in anhydrous ethanol for 1 hour to 2 hours, and then ultrasonic stirring is used for a second sufficient stirring to obtain a first ethanol mixed solution of a first group of lithium ion batteries, wherein the ultrasonic frequency range of the ultrasonic stirring is 15KHz to 50KHz, and the stirring time of the ultrasonic stirring is 0.5 h to 1.5 h; after the second sufficient stirring, the first ethanol mixed solution is centrifuged to obtain solid particles of the first ethanol mixed solution, and the solid particles of the first ethanol mixed solution are used as the first test material for the first group of lithium ion batteries.
[0050] In one embodiment, the second material to be tested in the positive electrode active material of the second group of lithium ion batteries can be obtained according to the positive electrode sheet of the second group of lithium ion batteries; the steps include: Step 2221, scrape powder from the positive electrode plates of the second group of lithium-ion batteries, separate the coating of the positive electrode plates of the second group of lithium-ion batteries from the positive electrode collector, and obtain a second powder material for the second group of lithium-ion batteries.
[0051] Step 2222: Disperse the second powder in an organic solvent to obtain a second mixed solution of a second group of lithium-ion batteries.
[0052] Step 2223, allowing the second mixed solution to stand for a set standing time, so that the second mixed solution is separated into an upper layer solution and a lower layer solution.
[0053] Step 2224, removing the upper layer solution of the second mixed solution, retaining the lower layer solution of the second mixed solution, and performing solid-liquid separation on the lower layer solution of the second mixed solution by centrifugation to obtain second powder particles of the second group of lithium-ion batteries.
[0054] Step 2225, dispersing the second powder particles in ethanol to obtain a second ethanol mixed solution of a second group of lithium-ion batteries.
[0055] Step 2226, centrifugally separate the second ethanol mixed solution to obtain second solid particles of the second ethanol mixed solution, and use the second solid particles as the second material to be tested.
[0056] In one embodiment, the specific process of obtaining the second material to be tested of the second group of lithium-ion batteries may refer to the specific process of obtaining the first material to be tested of the first group of lithium-ion batteries, which will not be described in detail here.
[0057] In one embodiment, the chemical formula of the positive electrode active material of the first group of lithium ion batteries and the second group of lithium ion batteries can be expressed as LiCo3-xO4M x ; Wherein, 0.1%≤x≤1%, M represents a doping element, including but not limited to one or more of Mg (magnesium), Ti (titanium), Ni (nickel), Mn (manganese), Na (sodium), Ca (calcium), P (phosphorus), La (lanthanum), Ce (cerium), Zr (zirconium), Y (yttrium), and Cd (cadmium).
[0058] In one embodiment, the organic solvent in step 2212 and step 2222 may include one or more of nitrogen-methyl pyrrolidone, acetone, dimethylformamide, dimethylacetamide, and anhydrous ethanol.
[0059] In one embodiment, the first material to be tested of the first group of lithium-ion batteries may include lithium cobalt oxide and / or cobalt oxide.
[0060] In one embodiment, the second material to be tested of the second group of lithium-ion batteries may include lithium cobalt oxide and / or cobalt oxide.
[0061] In the embodiment of the present application, the first powder particles and the second powder particles are respectively soaked in anhydrous ethanol, and the electrolyte on the particle surfaces of the first powder particles and the second powder particles are respectively cleaned by anhydrous ethanol. The volatility of anhydrous ethanol is strong, and the cleaned first powder particles and the second powder particles can be quickly dried to avoid unnecessary chemical reactions between the first powder particles and the second powder particles and the air. Through ultrasonic stirring, the first powder particles and the second powder particles are respectively fully dispersed in the anhydrous ethanol to achieve a better cleaning effect.
[0062] Step 230 , respectively determining a first cobalt content of the cobalt element in the first material to be tested of the first group of lithium ion batteries and a second cobalt content of the cobalt element in the second material to be tested of the second group of lithium ion batteries.
[0063] In one embodiment, a first cobalt content of the cobalt element in the first material to be tested of the first group of lithium-ion batteries can be obtained according to the first material to be tested of the first group of lithium-ion batteries; the steps include: Step 2311 , mixing a first material to be tested with a first hydrochloric acid solution, and performing a first heating treatment to prepare a first mixed solution of a first group of lithium-ion batteries.
[0064] In one embodiment, the first material to be tested of the first group of lithium-ion batteries may be mixed with the first hydrochloric acid solution and subjected to a first heating treatment to prepare a first mixed solution of the first group of lithium-ion batteries.
[0065] In one embodiment, the ratio of the mass of the first material to be tested to the volume of the first hydrochloric acid solution is 0.05-0.075; wherein the unit of the mass of the first material to be tested is gram, and the unit of the volume of the first hydrochloric acid solution is milliliter.
[0066] Step 2312, using a filter membrane to filter the first mixed solution to obtain the residue of the first mixed solution.
[0067] Step 2313, use high-purity water to rinse the residue and filter membrane of the first mixed solution a set number of times.
[0068] In one embodiment, the first mixed liquid of the first group of lithium-ion batteries can be filtered using filter membranes to separate the liquid and residue of the first mixed liquid to obtain the residue of the first mixed liquid; the residue of the first mixed liquid and the filter membrane can be rinsed a set number of times using high-purity water to clean the substances dissolved in the first hydrochloric acid solution, leaving only the residue of the first mixed liquid and the filter membrane.
[0069] Step 2314, mixing the residue of the washed first mixed solution and the filter membrane with the second hydrochloric acid solution, and performing a second heating treatment to obtain a third mixed solution of the first group of lithium-ion batteries.
[0070] In one embodiment, the residue of the first mixed solution after rinsing can be mixed with the filter membrane and the second hydrochloric acid solution, and a second heating treatment can be performed until the filter membrane is dissolved to eliminate the effect of the filter membrane on the test accuracy, thereby obtaining a third mixed solution of the first group of lithium-ion batteries.
[0071] Step 2315, mixing the third mixed solution with the perchloric acid solution, and performing a third heating treatment to allow the third mixed solution and the perchloric acid solution to fully react, thereby obtaining a first test solution of the first group of lithium-ion batteries.
[0072] In one embodiment, the ratio of the mass of the first material to be tested to the volume of the perchloric acid solution is 0.25-0.5; wherein the mass of the first material to be tested is in grams, and the volume of the perchloric acid solution is in milliliters.
[0073] In one embodiment, a container can be used to mix the third mixed solution of the first group of lithium ion batteries with a perchloric acid solution, and a third heating treatment can be performed until perchloric acid smoke is generated and the perchloric acid smoke rises to the container mouth for 30 seconds to 50 seconds, so that the third mixed solution and the perchloric acid solution are fully reacted, and the mixture is cooled to room temperature to obtain a first test solution of the first group of lithium ion batteries.
[0074] Step 2316, obtaining a first cobalt content of the cobalt element in the first test liquid, and taking the first cobalt content of the cobalt element in the first test liquid as the first cobalt content M1 of the cobalt element in the first test material of the first group of lithium-ion batteries.
[0075] In one embodiment, an inductively coupled plasma emission spectrometer can be used to obtain the content of cobalt in the first test liquid; based on the content of cobalt in the first test liquid, a first cobalt content M1 of the cobalt in the first test material of the first group of lithium-ion batteries is determined.
[0076] In one embodiment, a second cobalt content of the cobalt element in the second material to be tested of the second group of lithium ion batteries can be obtained according to the second material to be tested of the second group of lithium ion batteries; the steps include: Step 2321 , mixing the second material to be tested with the first hydrochloric acid solution, and performing a first heating treatment to prepare a second mixed solution of a second group of lithium-ion batteries.
[0077] In one embodiment, the ratio of the mass of the second material to be tested to the volume of the first hydrochloric acid solution is 0.05-0.075; wherein the unit of the mass of the second material to be tested is gram, and the unit of the volume of the first hydrochloric acid solution is milliliter.
[0078] Step 2322, use a filter membrane to filter the second mixed liquid to obtain the residue of the second mixed liquid.
[0079] Step 2323, use high-purity water to rinse the residue and filter membrane of the second mixed solution a set number of times.
[0080] Step 2324, mixing the residue of the rinsed second mixed solution and the filter membrane with the second hydrochloric acid solution, and performing a second heating treatment to obtain a fourth mixed solution of the second group of lithium-ion batteries.
[0081] Step 2325, mixing the fourth mixed solution with the perchloric acid solution, and performing a third heating treatment to allow the fourth mixed solution and the perchloric acid solution to fully react, thereby obtaining a second test solution of the second group of lithium-ion batteries.
[0082] In one embodiment, the ratio of the mass of the second material to be tested to the volume of the perchloric acid solution is 0.25-0.5; wherein the mass of the second material to be tested is in grams, and the volume of the perchloric acid solution is in milliliters.
[0083] Step 2326, obtaining a second cobalt content of the cobalt element in the second test liquid, and taking the second cobalt content of the cobalt element in the second test liquid as the second cobalt content M2 of the cobalt element in the second test material of the second group of lithium-ion batteries.
[0084] In one embodiment, the specific process of obtaining the second cobalt content of the cobalt element in the second material to be tested of the second group of lithium ion batteries can refer to the specific process of obtaining the first cobalt content of the cobalt element in the first material to be tested of the first group of lithium ion batteries, which will not be repeated here.
[0085] In one embodiment, the mass percentage concentration of the first hydrochloric acid solution in step 2321 and step 2311 is 20% to 25%.
[0086] In one embodiment, the first heating temperature of the first heating treatment in step 2321 and step 2311 is 100° C. to 150° C., and the first heating time of the first heating treatment is 30 min (minutes) to 50 min. The first heating treatment can fully react the first material to be tested with the first hydrochloric acid solution, and the second material to be tested with the first hydrochloric acid solution.
[0087] In one embodiment, the mass percentage concentration of the second hydrochloric acid solution in step 2324 and step 2314 is 25% to 30%.
[0088] In one embodiment, the second heating temperature of the second heating treatment in step 2324 and step 2314 is 200° C. to 400° C., and the second heating time of the second heating treatment is 30 min to 50 min. The second heating treatment can fully react the residue of the first mixed solution, the filter membrane, and the second hydrochloric acid solution, and the residue of the second mixed solution, the filter membrane, and the second hydrochloric acid solution.
[0089] In one embodiment, the filter membrane in step 2322 and step 2312 may be a water filter membrane, and the filter pore size of the filter membrane may be 0.1 μm (micrometer) to 1.0 μm. Using a soluble water filter membrane can prevent the filter membrane from affecting the data accuracy of the first cobalt content M1 and the second cobalt content M2.
[0090] Step 240, calculating a first mass proportion of cobalt oxide in the positive electrode active material of the first group of lithium ion batteries according to the first cobalt content; and calculating a second mass proportion of cobalt oxide in the positive electrode active material of the second group of lithium ion batteries according to the second cobalt content.
[0091] In one embodiment, the first mass proportion ω1 of cobalt oxide in the positive electrode active material of the first group of lithium ion batteries can be calculated according to the first cobalt content M1 of the first group of lithium ion batteries, the volume V1 of the first test liquid, and the mass m1 of the first test material, wherein: ω1(%)=0.1365×(M1)×(V1)×(m1).
[0092] In one embodiment, 0.1365 is a constant, the unit of the first cobalt content M1 is mg / L (milligrams per liter), the unit of the volume V1 of the first test liquid is L (liter), and the unit of the mass m1 of the first test material is g (gram).
[0093] In one embodiment, the second mass proportion ω2 of cobalt oxide in the positive electrode active material of the second group of lithium ion batteries can be calculated according to the second cobalt content M2 of the second group of lithium ion batteries, the volume V2 of the second test liquid, and the mass m2 of the second test material, wherein: ω2(%)=0.1365×(M2)×(V2)×(m2).
[0094] In one embodiment, 0.1365 is a constant, the unit of the second cobalt content M2 is mg / L (milligrams per liter), the unit of the volume V2 of the second test liquid is L (liter), and the unit of the mass m2 of the second test material is g (gram).
[0095] Step 250, calculating the degree of structural degradation of the positive electrode active material characterizing failure of the positive electrode active material of the lithium ion battery according to the first mass ratio of cobalt oxide in the positive electrode active material of the first group of lithium ion batteries and the second mass ratio of cobalt oxide in the positive electrode active material of the second group of lithium ion batteries.
[0096] In one embodiment, the positive electrode active material structural degradation degree θ characterizing the failure of the positive electrode active material of the lithium ion battery can be calculated according to the first mass proportion ω1 of cobalt oxide in the positive electrode active material of the first group of lithium ion batteries and the second mass proportion ω2 of cobalt oxide in the positive electrode active material of the second group of lithium ion batteries, wherein: .
[0097] In one embodiment, the greater the positive electrode active material structure degradation degree θ that characterizes the failure of the positive electrode active material of the lithium ion battery, the greater the degree of structural degradation of the positive electrode active material of the lithium ion battery; wherein, When 0≤θ≤30%, it means that the structure of the positive electrode active material of the lithium-ion battery is basically not degraded; When 30%<θ≤60%, it indicates that the structure of the positive electrode active material of the lithium-ion battery is slightly degraded; When 60%<θ≤90%, it indicates that the structure of the positive electrode active material of the lithium-ion battery is moderately degraded; When θ>90%, it indicates that the structure of the positive electrode active material of the lithium-ion battery is seriously degraded.
[0098] The method for analyzing failure of positive electrode active materials of lithium ion batteries in the embodiments of the present application calculates the degree of structural degradation of the positive electrode active materials of the lithium ion batteries after the cycle test by the mass proportion of cobalt oxide in the positive electrode active materials of the lithium ion batteries before and after the cycle test. The greater the degree of structural degradation of the positive electrode active materials, the more serious the failure of the positive electrode active materials. The degree of structural degradation of the phase structure of the positive electrode active materials (lithium cobalt oxide) of the lithium ion batteries after the cycle test is quantitatively analyzed, and the failure of the positive electrode active materials of the lithium ion batteries can be quantitatively analyzed and the failure of the positive electrode active materials of the lithium ion batteries can be quantitatively characterized.
[0099] Furthermore, the method for analyzing the failure of the positive electrode active material of a lithium ion battery of the embodiment of the present application separates the lithium cobalt oxide and the cobalt oxide in the positive electrode active material of the lithium ion battery by physical and chemical methods to achieve quantitative testing of the cobalt oxide, and calculates the degree of structural degradation of the positive electrode active material that characterizes the failure of the positive electrode active material of the lithium ion battery according to the first mass ratio of the cobalt oxide in the positive electrode active material of the first group of lithium ion batteries and the second mass ratio of the cobalt oxide in the positive electrode active material of the second group of lithium ion batteries. The process is relatively simple and the cost is low, and it can be used as a conventional means for analyzing the failure of the positive electrode active material; and it can quantitatively analyze the degree of structural degradation of the phase structure of the positive electrode active material (lithium cobalt oxide) of the lithium ion battery after the cycle test, can quantitatively analyze the failure of the positive electrode active material of the lithium ion battery, and quantitatively characterize the failure of the positive electrode active material of the lithium ion battery, which can have a strong guiding significance for the improvement direction of the positive electrode active material, provide data support for the improvement of the positive electrode active material of the lithium ion battery, and make the selection of the positive electrode active material in the lithium ion battery cell system and the improvement direction of the positive electrode active material more targeted.
[0100] The stability and effectiveness of the failure analysis method for the positive electrode active material of a lithium-ion battery of the present application are further described below through specific examples.
[0101] Embodiment 1: In Example 1, one fresh soft-pack battery cell of each of the three groups A / B / C of single factor comparison positive electrode active materials can be taken, and the soft-pack battery cells can be disassembled and 100 cm in size can be taken. 2 The positive electrode sheet is prepared by using a ceramic knife to separate the coating on the positive electrode sheet from the foil; the scraped powder is soaked in nitrogen methyl pyrrolidone for ultrasonic stirring, the ultrasonic frequency range is 15KHz ~ 50KHz, and the stirring time is 3h; the upper conductive agent is taken out from the mixed solution after ultrasonication with a rubber-tipped dropper, and the remaining mixed solution is separated into solid and liquid by a centrifuge, and the separated powder particles are soaked in anhydrous ethanol for 1h; then ultrasonic stirring is performed again, the ultrasonic frequency range is 15KHz ~ 50KHz, and the stirring time is 0.5h. After the stirring is completed, centrifugal separation is performed again, and finally the powder particles are collected as the material to be tested for the next step of processing.
[0102] 1.0 g of the material to be tested was placed in a 100 mL conical flask, and heated with 20 ml of a 20% by mass hydrochloric acid solution at 100°C for about 30 min, and a first mixed solution was obtained after the material to be tested and the hydrochloric acid were fully reacted; the first mixed solution was filtered using a water filter membrane with a pore size of 0.1 μm, and the residue and the filter membrane were rinsed 3 times with high-purity water; the rinsed residue and the filter membrane were heated with 20 ml of a 25% by mass hydrochloric acid solution at 200°C for about 30 min until the filter membrane was completely dissolved, and a A third mixed solution was obtained; the third mixed solution and 3 ml of a 65% by mass perchloric acid solution were heated and dissolved at 500° C. until perchloric acid smoke came out of the bottle mouth, and then the mixture was removed and cooled to room temperature to obtain the test solutions corresponding to the three groups A / B / C respectively; the Co contents corresponding to the three groups A / B / C of Co (cobalt) elements in the test solutions were determined by an inductively coupled plasma emission spectrometer, and the mass proportions of cobalt oxide corresponding to the three groups A / B / C of Co (cobalt) elements in the test materials were calculated according to the Co contents.
[0103] The three groups of test materials corresponding to A / B / C were tested according to the above steps, tested twice a day for 1 week, to verify the failure analysis method of the positive active material of the lithium ion battery in the embodiment of the present application, to obtain the stability of the mass proportion of cobalt oxide in the positive active material of the lithium ion battery, to verify the failure analysis method of the positive active material of the lithium ion battery in the embodiment of the present application, and to calculate the stability of the structural degradation degree of the positive active material that characterizes the failure of the positive active material of the lithium ion battery. The specific test data are shown in Table 1.
[0104] Embodiment 2: In Example 2, one fresh soft-pack battery cell of each of the three groups of single-factor comparison positive electrode active materials A / B / C in Example 1 can be taken, and a cycle test can be performed on the fresh soft-pack battery cell at 45°C. The cycle test includes: 1.2C constant current and constant voltage charging to 4.53V, 0.05C cut-off, 0.7C discharge to 3V, and 400 cycles.
[0105] The three soft-pack cells after the cycle test were disassembled, and the mass proportion of cobalt oxide in the positive electrode active material of the lithium-ion battery was obtained according to the process of obtaining the mass proportion of cobalt oxide in the positive electrode active material of the lithium-ion battery in Example 1, and the mass proportion of cobalt oxide in the positive electrode active material of the three soft-pack cells after the cycle test was obtained. Each soft-pack cell was tested twice and the average was taken, and the positive electrode active material structure degradation degree θ that characterizes the failure of the positive electrode active material of the lithium-ion battery was calculated respectively. The test data is shown in Table 2.
[0106] It can be seen from the test data in Table 1 that the three groups of samples A / B / C were tested continuously for one week, and the RSD (Relative Standard Deviation) of the mass proportion of cobalt oxide in the positive electrode active material obtained was less than 10%, which proves that the failure analysis method of the positive electrode active material of the lithium ion battery in the embodiment of the present application can stably obtain the mass proportion of cobalt oxide in the positive electrode active material, and the accuracy of the obtained mass proportion of cobalt oxide in the positive electrode active material can meet the requirements of failure analysis of the positive electrode active material of the lithium ion battery.
[0107] It can be seen from the test data in Table 2 that after 400 weeks of cycle testing at 45°C, the three groups of fresh soft-pack batteries A / B / C all have a certain degree of capacity loss, accompanied by varying degrees of increase in cobalt oxide content. The increase in cobalt oxide content indicates that the phase structure of the cobalt oxide positive active material has undergone structural degradation. According to the test data in Table 2, the 400-week capacity retention rate of group A samples is the highest, and the structural degradation degree θ of the positive active material characterizing the failure of the positive active material of the lithium-ion battery is the smallest; the capacity retention rate of group C samples is the lowest, and the structural degradation degree θ of the positive active material characterizing the failure of the positive active material of the lithium-ion battery is the largest, indicating that the structural degradation degree θ of the positive active material can be used to characterize the failure of the positive active material of the lithium-ion battery, and the difference in the phase structure failure of the positive active material of different lithium-ion batteries can be compared by comparing the structural degradation degree θ of the positive active material. Therefore, the method for analyzing the failure of the positive electrode active material of a lithium ion battery in the embodiment of the present application separates the lithium cobalt oxide and the cobalt oxide in the positive electrode active material of the lithium ion battery by physical and chemical methods to achieve quantitative testing of the cobalt oxide. According to the first mass ratio of the cobalt oxide in the positive electrode active material of the first group of lithium ion batteries and the second mass ratio of the cobalt oxide in the positive electrode active material of the second group of lithium ion batteries, the degree of structural degradation of the positive electrode active material that characterizes the failure of the positive electrode active material of the second group of lithium ion batteries is calculated. The process is relatively simple and the cost is low, and it can be used as a conventional means for analyzing the failure of the positive electrode active material; and the degree of structural degradation of the phase structure of the positive electrode active material (lithium cobalt oxide) of the lithium ion battery after the cycle test can be quantitatively analyzed, the failure of the positive electrode active material of the lithium ion battery can be quantitatively analyzed, and the failure of the positive electrode active material of the lithium ion battery can be quantitatively characterized, which can have a strong guiding significance for the improvement direction of the positive electrode active material, provide data support for the improvement of the positive electrode active material of the lithium ion battery, and make the selection of the positive electrode active material in the lithium ion battery cell system and the improvement direction of the positive electrode active material more targeted.
[0108] According to the test data in Table 2, the capacity retention rate of group C samples is the lowest, and the positive electrode active material structure degradation degree θ, which characterizes the failure of the positive electrode active material of the lithium-ion battery, of group C samples is also the largest. According to the positive electrode active material structure degradation degree θ of group C samples, it can be analyzed that one of the main reasons for the loss of battery cell capacity of group C samples is that the phase structure of the positive electrode active material is seriously degraded. When the positive electrode active material of group C samples is subsequently optimized, the stability of the phase structure of the positive electrode active material can be enhanced, and the degradation of the phase structure of the positive electrode active material of group C samples can be inhibited.
[0109] Table 1:
[0110] Table 2:
[0111] Figure 3 It is a schematic diagram of the structure of an electronic device shown in an embodiment of the present application.
[0112] See also Figure 3 , the electronic device 1000 includes a memory 1010 and a processor 1020 .
[0113] The processor 1020 may be a central processing unit (CPU), or other general-purpose processors, digital signal processors (DSP), application-specific integrated circuits (ASIC), field-programmable gate arrays (FPGA), or other programmable logic devices, discrete gate or transistor logic devices, discrete hardware components, etc. A general-purpose processor may be a microprocessor or the processor may be any conventional processor, etc.
[0114] The memory 1010 may include various types of storage units, such as system memory, read-only memory (ROM), and permanent storage devices. Among them, ROM can store static data or instructions required by the processor 1020 or other modules of the computer. The permanent storage device may be a readable and writable storage device. The permanent storage device may be a non-volatile storage device that does not lose the stored instructions and data even after the computer is powered off. In some embodiments, the permanent storage device uses a large-capacity storage device (such as a magnetic or optical disk, flash memory) as a permanent storage device. In some other embodiments, the permanent storage device may be a removable storage device (such as a floppy disk, optical drive). The system memory may be a readable and writable storage device or a volatile readable and writable storage device, such as a dynamic random access memory. The system memory may store some or all instructions and data required by the processor at runtime. In addition, the memory 1010 may include any combination of computer-readable storage media, including various types of semiconductor storage chips (such as DRAM, SRAM, SDRAM, flash memory, programmable read-only memory), and disks and / or optical disks may also be used. In some embodiments, the memory 1010 may include a readable and / or writable removable storage device, such as a laser disc (CD), a read-only digital versatile disc (such as a DVD-ROM, a double-layer DVD-ROM), a read-only Blu-ray disc, an ultra-density optical disc, a flash memory card (such as an SD card, a mini SD card, a Micro-SD card, etc.), a magnetic floppy disk, etc. The computer-readable storage medium does not include carrier waves and transient electronic signals transmitted wirelessly or wired.
[0115] The memory 1010 stores executable codes, and when the executable codes are processed by the processor 1020 , the processor 1020 can execute part or all of the methods described above.
[0116] In addition, the method according to the present application may also be implemented as a computer program or a computer program product, which includes computer program code instructions for executing some or all of the steps in the above method of the present application.
[0117] Alternatively, the present application can also be implemented as a computer-readable storage medium (or non-transitory machine-readable storage medium or machine-readable storage medium) on which executable code (or computer program or computer instruction code) is stored. When the executable code (or computer program or computer instruction code) is executed by a processor of an electronic device (or server, etc.), the processor executes part or all of the steps of the above-mentioned method according to the present application.
[0118] The embodiments of the present application have been described above, and the above description is exemplary, not exhaustive, and is not limited to the disclosed embodiments. Many modifications and changes will be apparent to those of ordinary skill in the art without departing from the scope and spirit of the described embodiments. The selection of terms used herein is intended to best explain the principles of the embodiments, practical applications, or improvements to the technology in the market, or to enable other persons of ordinary skill in the art to understand the embodiments disclosed herein.
Claims
1. A method for analyzing failure of positive electrode active materials of lithium ion batteries, characterized in that: include: Obtain a first group of lithium-ion batteries and a second group of lithium-ion batteries, wherein the first group of lithium-ion batteries includes a group of fresh fully-charged lithium-ion batteries that have not been cycled tested, and the second group of lithium-ion batteries includes another group of fresh fully-charged lithium-ion batteries that have been cycled tested; The degree of structural degradation of the positive electrode active material characterizing failure of the positive electrode active material of the lithium ion battery is calculated based on a first mass ratio of cobalt oxide in the positive electrode active material of the first group of lithium ion batteries and a second mass ratio of cobalt oxide in the positive electrode active material of the second group of lithium ion batteries.
2. The method according to claim 1, characterized in that Before calculating the degree of structural degradation of the positive electrode active material characterizing failure of the positive electrode active material of the lithium ion battery according to the first mass proportion of cobalt oxide in the positive electrode active material of the first group of lithium ion batteries and the second mass proportion of cobalt oxide in the positive electrode active material of the second group of lithium ion batteries, the method comprises: Obtaining a first material to be tested from the positive electrode active materials of the first group of lithium-ion batteries; According to the first material to be tested, obtaining the first mass ratio; Obtaining a second material to be tested from the positive electrode active material of the second group of lithium-ion batteries; According to the second material to be tested, the second mass ratio is obtained.
3. The method according to claim 2, characterized in that The step of obtaining a first material to be tested from the positive electrode active materials of the first group of lithium-ion batteries comprises: Scraping powder from the positive electrode sheets of the first group of lithium-ion batteries to separate the coating of the positive electrode sheets from the positive electrode current collector to obtain a first powder material of the first group of lithium-ion batteries; Dispersing the first powder in an organic solvent to obtain a first mixed solution of the first group of lithium-ion batteries; The first mixed solution is allowed to stand for a set standing time, so that the first mixed solution is separated into an upper layer solution and a lower layer solution; removing the upper layer solution of the first mixed solution, retaining the lower layer solution of the first mixed solution, and performing solid-liquid separation on the lower layer solution of the first mixed solution by centrifugation to obtain first powder particles of the first group of lithium-ion batteries; Dispersing the first powder particles in ethanol to obtain a first ethanol mixed solution of the first group of lithium-ion batteries; Centrifugally separating the first ethanol mixed solution to obtain first solid particles of the first ethanol mixed solution, and using the first solid particles as the first material to be tested; and / or, The step of obtaining the second material to be tested from the positive electrode active material of the second group of lithium-ion batteries comprises: Scraping powder from the positive electrode sheets of the second group of lithium-ion batteries to separate the coating on the positive electrode sheets of the second group of lithium-ion batteries from the positive electrode current collector to obtain a second powder material for the second group of lithium-ion batteries; Dispersing the second powder in an organic solvent to obtain a second mixed solution of the second group of lithium-ion batteries; The second mixed solution is allowed to stand for a set standing time, so that the second mixed solution is separated into an upper layer solution and a lower layer solution; removing the upper layer solution of the second mixed solution, retaining the lower layer solution of the second mixed solution, and performing solid-liquid separation on the lower layer solution of the second mixed solution by centrifugation to obtain second powder particles of the second group of lithium-ion batteries; Dispersing the second powder particles in ethanol to obtain a second ethanol mixed solution of the second group of lithium ion batteries; The second ethanol mixed solution is centrifuged to obtain second solid particles of the second ethanol mixed solution, and the second solid particles are used as the second material to be tested.
4. The method according to claim 2, characterized in that: The obtaining the first mass ratio according to the first material to be tested includes: Mixing the first material to be tested with a first hydrochloric acid solution and performing a first heating treatment to prepare a first mixed solution of the first group of lithium-ion batteries; Using a filter membrane to filter the first mixed solution to obtain a residue of the first mixed solution; Using high-purity water to rinse the residue of the first mixed solution and the filter membrane for a set number of times; The residue of the first mixed solution after washing is mixed with the filter membrane and the second hydrochloric acid solution, and subjected to a second heating treatment to obtain a third mixed solution of the first group of lithium-ion batteries; Mixing the third mixed solution with a perchloric acid solution, and performing a third heating treatment to allow the third mixed solution and the perchloric acid solution to fully react, thereby obtaining a first test solution of the first group of lithium-ion batteries; Obtaining a first cobalt content of the cobalt element in the first test solution; calculating the first mass proportion according to the first cobalt content, the volume of the first test liquid, and the mass of the first test material; and / or, The step of obtaining the second mass ratio according to the second material to be tested includes: Mixing the second material to be tested with the first hydrochloric acid solution and performing a first heating treatment to prepare a second mixed solution of the second group of lithium-ion batteries; Using a filter membrane to filter the second mixed liquid to obtain a residue of the second mixed liquid; Using high-purity water to rinse the residue of the second mixed solution and the filter membrane for a set number of times; Mixing the residue of the second mixed solution after washing with the filter membrane and the second hydrochloric acid solution, and performing a second heating treatment to obtain a fourth mixed solution of the second group of lithium-ion batteries; Mixing the fourth mixed solution with a perchloric acid solution, and performing a third heating treatment to allow the fourth mixed solution and the perchloric acid solution to fully react, thereby obtaining a second test solution of the second group of lithium-ion batteries; Obtaining a second cobalt content of the cobalt element in the second test solution; The second mass proportion is calculated according to the second cobalt content, the volume of the second test liquid, and the mass of the second test material.
5. The method according to claim 4, characterized in that The calculating the first mass ratio according to the first cobalt content, the volume of the first test liquid, and the mass of the first test material includes: The first mass proportion ω1 is calculated using the following formula: ω1(%)=0.1365×(M1)×(V1)×(m1); Wherein, M1 represents the first cobalt content, V1 represents the volume of the first test liquid, and m1 represents the mass of the first test material; and / or, The calculating the second mass proportion according to the second cobalt content, the volume of the second test liquid, and the mass of the second test material includes: The second mass proportion ω2 is calculated using the following formula: ω2(%)=0.1365×(M2)×(V2)×(m2); In the formula, M2 represents the second cobalt content, V2 represents the volume of the second test liquid, and m2 represents the mass of the second test material.
6. The method according to claim 3, characterized in that: The organic solvent includes one or more of nitrogen-methyl pyrrolidone, acetone, dimethylformamide, dimethylacetamide, and anhydrous ethanol.
7. The method according to claim 4, characterized in that: The mass percentage concentration of the first hydrochloric acid solution is 20% to 25%; The first heating temperature of the first heating treatment is 100° C. to 150° C., and the first heating time of the first heating treatment is 30 min to 50 min.
8. The method according to claim 4, characterized in that: The ratio of the mass of the first material to be tested to the volume of the first hydrochloric acid solution is 0.05 to 0.075; The ratio of the mass of the second material to be tested to the volume of the first hydrochloric acid solution is 0.05 to 0.075; wherein, The unit of the mass of the first material to be tested and the unit of the mass of the second material to be tested is gram, and the unit of the volume of the first hydrochloric acid solution is milliliter.
9. The method according to claim 4, characterized in that: The filter membrane is a water filter membrane, and the pore size of the filter membrane is 0.1 μm to 1.0 μm.
10. The method according to claim 4, characterized in that: The mass percentage concentration of the second hydrochloric acid solution is 25% to 30%; The second heating temperature of the second heating treatment is 200° C. to 400° C., and the second heating time of the second heating treatment is 30 min to 50 min.
11. The method according to claim 4, characterized in that: The mass percentage concentration of the perchloric acid solution is 65% to 70%; The third heating temperature of the third heat treatment is 500°C to 800°C.
12. The method according to claim 4, characterized in that: The ratio of the mass of the first material to be tested to the volume of the perchloric acid solution is 0.25 to 0.5; The ratio of the mass of the second material to be tested to the volume of the perchloric acid solution is 0.25 to 0.5; wherein, The unit of the mass of the first material to be tested and the unit of the mass of the second material to be tested is gram, and the unit of the volume of the perchloric acid solution is milliliter.